Comparison of clinical efficacy of three different dentin matrix biomaterials obtained from different devices. (3rd April 2023) - Dłucik, Robert; Orzechowska-Wylęgała, Bogusława; Dłucik, Daniel; Puzzolo, Domenico; Santoro, Giuseppe; Micali, Antonio; Testagrossa, Barbara; Acri, Giuseppe
ABSTRACT: Aim: The aim of the present study was to propose the clinical efficacy of the different dentin matrix obtained from three devices (BonMaker, Tooth Transformer, and Smart Dentin Grinder) and to show their morphological, physical, and biochemical characteristics using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy, and Raman spectroscopy. Research design and methods: The study included 70 patients who underwent bone augmentation using the BonMaker, Tooth Transformer, and Smart Dentin Grinder devices. In addition, 84 implants were placed. Furthermore, four samples, one for each device and one non-demineralized control, were analyzed with scanning electron microscopy (SEM), energy-dispersive X-ray analysis, and Raman spectroscopy. Results: In all patients, augmentation of bone defects with ground dentin matrix was successful, and implants showed correct osseointegration. The morphological organization, the chemical composition, and the presence of organic molecules in the dentin samples processed by the three different devices were demonstrated using SEM, energy-dispersive X-ray analysis, and Raman spectroscopy. Conclusions: Comparing BonMaker, Tooth Transformer, and Smart Dentin Grinder devices in our practice, we concluded that these systems, even with different structural and chemical differences of the dentin granules, have a comparable potential for obtaining regenerative material from the patient's own teeth.